Development Of Spray Gel From Ethanol Extract Of Bamboo (Polygonum pulchrum Blume) Plants Using Viskolam® and Hydroxypropyl Methyl Cellulose (HPMC) Gel Combination Base - Wa O.S. Zubaydah; Vica Aspadiah; Muhammad Ammar (MEDULA: Jurnal Ilmiah Fakultas Kedokteran Universitas Halu Oleo, 2022)
Background: Bamboo plants are one of the traditional medicinal plants that are often used by the community. The stem of Polygonum pulchrum Blume contains a triterpenoid steroid compound that acts as an active antioxidant. Purpose: This study aims to determine the optimal formula for spray gel preparation of P. pulchrum Blume ethanol extract using Design Expert®. Methods: The stems of P. pulchrum Blume were extracted by maceration using 96% ethanol to obtain a thick extract. The extract obtained was formulated with spray gel preparations with variations in the concentration of viscolam® and HPMC F1(0,1%:0,1%), F2(0,4%:0,1%), F3(0,4%:0, 4%), and F4(0,1%:0,4%). The test was carried out by looking at the characteristics consisting of same tests: organoleptic, pH, viscosity, spray pattern, dry time and homogenity, and also to determined the stability of the spray gel before and after the cycling test. Optimization of the spray gel formula using a factorial design of 23 with a viscolam® factor and HPMC using dry time response, viscosity, and spraying pattern. After obtaining the optimum formula, hedonic testing was carried out by looking at the parameters of color, aroma, texture, and overall appearance. Results: The results showed that the optimum formula for the F2 formula was the concentration of viscolam® and HPMC 0.4%: 0.1%, as well as spray gel preparations that had been evaluated for stability and had met the stability test requirements based on the test parameters. Conclusion: the optimal formula for spray gel preparation of P. pulchrum Blume ethanol extract using Design Expert® was a formula with a combination of viscolam® gel and HPMC 0.4% : 0.1%.